2005
DOI: 10.1074/jbc.m403080200
|View full text |Cite
|
Sign up to set email alerts
|

Genes Affecting the Cell Cycle, Growth, Maintenance, and Drug Sensitivity Are Preferentially Regulated by Anti-HER2 Antibody through Phosphatidylinositol 3-Kinase-AKT Signaling

Abstract: The molecular mechanisms by which the anti-HER2 antibodies trastuzumab and its murine equivalent 4D5 inhibit tumor growth and potentiate chemotherapy are not fully understood. Inhibition of signaling through the phosphatidylinositol 3-kinase (PI3K)-AKT pathway may be particularly important. Treatment of breast cancer cells that overexpress HER2 with trastuzumab inhibited HER2-HER3 association, decreased PDK1 activity, reduced Thr-308 and Ser-473 phosphorylation of AKT, and reduced AKT enzymatic activity. To pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 38 publications
6
67
0
Order By: Relevance
“…HER2 siRNA treatment of HER2-overexpressing BT474 cells also increases TSP-1 expression (Yang et al, 2004). Affymetrix microarray analysis indicated that treatment of BT474 cells with trastuzumab elevates TSP-1 expression (Le et al, 2005a). In this report, we showed that HER2 signaling closely regulated TSP-1 expression (Figure 3), which supports the notion that trastuzumab-induced TSP-1 expression (Figures 4 and 6) may contribute to tumor growth inhibition.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…HER2 siRNA treatment of HER2-overexpressing BT474 cells also increases TSP-1 expression (Yang et al, 2004). Affymetrix microarray analysis indicated that treatment of BT474 cells with trastuzumab elevates TSP-1 expression (Le et al, 2005a). In this report, we showed that HER2 signaling closely regulated TSP-1 expression (Figure 3), which supports the notion that trastuzumab-induced TSP-1 expression (Figures 4 and 6) may contribute to tumor growth inhibition.…”
Section: Discussionsupporting
confidence: 79%
“…We next examined possible signaling pathways that could regulate expression of these angiogenic factors. One was PI3K-AKT, which is important for HER2 signaling, and inhibition of HER2 signaling with trastuzumab significantly inhibits PI3K-AKT signaling (Le et al, 2000(Le et al, , 2005a. It is also well documented that the PI3K-AKT pathway plays an important role in angiogenesis (Dimmeler and Zeiher, 2000;Jiang et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations